Menggali nilai pancasila dalam menyikapi kasus intoleransi di masyarakat - Sofi, Dini Febriana (Maliki Interdisciplinary Journal, 2025)
The phenomenon of intolerance in Indonesia, which is based on Pancasila principles, is a serious threat to social stability and individual rights. Even though Pancasila promotes tolerance and keberagaman, a number of factors, including a lack of understanding of Pancasila, an inadequate educational system, the influence of social media, extreme ideologies, and a lack of legal knowledge, contribute to the emergence of intolerance. Understanding the principles of Pancasila is crucial for preventing intolerance. Every Pancasila sila, starting from rituals related to religious observance to social interactions, helps to create a diverse community. Good education, constructive social interactions, and the use of social media in a timely manner can all help to strengthen this understanding. Tegas hukum penegakan is also necessary to ensure that intolerance is not violated. It is believed that by incorporating Pancasila principles into daily life, Indonesia will be able to bring about a more peaceful, adil, and united populace.